The effect of practice through repeated reading on gain in reading ability using a computer-based instructional system. - Carver, Ronald P.; Hoffman, James V. (Reading Research Quarterly (Wiley-Blackwell), 1981)
THE EFFECT OF READING PRACTICE in a ‘repeated readings’ format upon reading ability was investigated, using a computer-based instructional system. High school students who read poorly were given reading training using a recently developed technique called programmed prose, which allowed regular reading material to be automatically converted into training material. Each programmed prose passage was read and reread on a PLATO IV computer terminal until mastery was achieved. Each student was giver 50 to 70 hours of individualized instruction on the terminal: over 20 measures of progress were administered each hour. There were two separate studies with six high school students in each study. The results of Study 1 were replicated in Study 2. Specific gains in fluency on the practice task were clearly evident. On one measure of general reading ability, there was a large amount of gain from about Grade Level 5 to 8; however, on another general measure of reading ability, there was little or no evidence of gain. Hence, the effect of reading practice upon gain in reading ability may be limited. A theoretical interpretation of the findings is presented.